iCoverT: A rich data source on the incidence of child maltreatment over time in England and Wales - Degli Esposti, M; Taylor, J; Humphreys, D; Bowes, L (Public Library of Science, 2018)
Child maltreatment is a major public health problem, which is plagued with research challenges. Good epidemiological data can help to establish the nature and scope of past and present child maltreatment, and monitor its progress going forward. However, high quality data sources are currently lacking for England and Wales. We employed systematic methodology to harness pre-existing datasets (including non-digitalised datasets) and develop a rich data source on the incidence of Child maltreatment over Time (iCoverT) in England and Wales. The iCoverT consists of six databases and accompanying data documentation: Child Protection Statistics, Children In Care Statistics, Criminal Statistics, Homicide Index, Mortality Statistics and NSPCC Statistics. Each database is a unique indicator of child maltreatment incidence with 272 data variables in total. The databases span from 1858 to 2016 and therefore extends current data sources by over 80 years. We present a proof-of-principle analysis of a subset of the data to show how time series methods may be used to address key research challenges. This example demonstrates the utility of iCoverT and indicates that it will prove to be a valuable data source for researchers, clinicians and policy-makers concerned with child maltreatment.